DAMPAK KEBIJAKAN ANGGARAN PEMASARAN TERHADAP VOLUME PENJUALAN PRODUK MIE INSTAN PT INDOFOOD CBP SUKSES MAKMUR, TBK DI KOTA BAUBAU - Antasalam Ajo (Media Agribisnis, 2019)
This study aims to 1) analyze the influence of the marketing budget policy on the volume of product sales of instant noodles in the PT. Indofood CBP Sukses Makmur, Tbk in Baubau, 2) a portrait of the volume of product sales of instant noodles in the PT. Indofood CBP Sukses Makmur, Tbk in Baubau. In this study the research variables consisted of the dependent variable is the volume of sales, and independent variables consisting of distribution costs, advertising costs, costs outlets, and promotional costs. Apart from that necessary support is also variable: the number of workers, the number of receipts of goods, the amount of budget, schedule the use of budgets, types of sales activities, and the selling price. Data were analyzed using multiple linear regression analysis, and trend analysis of sales volume. The study produced several conclusions, among others, promotional costs, advertising costs, costs associated outlets and distribution costs and simultaneously positively and significantly influenced the partial volume of product sales of instant noodles in the PT. Indofood CBP Success prosperous, Tbk Baubau. Based on the value of elasticity, promotional expenses increased 1% then it will increase the sales volume of 0.004%, advertising expenses increased 1% then it will increase the sales volume of 0.002%, expenses increased 1% then the outlet will increase the sales volume of 0.001%, and distribution costs increased 1%, then will increase the sales volume of 0 001%. Volume sales of instant noodle products at PT. Indofood CBP Sukses Makmur, Tbk Baubau from 2010 to 2014 has increased by an average of 159.406 billion rupiahs per year while the year 2011 to 2015 the average sales volume will reach 197.315 billion rupiahs per year. Keywords: marketing budget policies and trends in sales volume.